IMPLEMENTASI KODE ETIK JURNALISTIK PADA BERITA KRIMINAL (BERITA PEMBUNUHAN) DI SURAT KABAR PEKANBARU MX - Prihandini. CH; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Community and news are two variable that are currently inseparable. In general, people put mass media function at the level of needs. Thus, reciprocation of the mass media business is partly determined by people‟s appreciation for the precentation of news in the mass media. The type crime news is presented in a variety of versions ranging from robbery, sexual assault, accident until the news of the murder. Information about crime news easier for people to know in detail about the security situation is happening arround their lives. Furthermore, the public can raise awareness and preventive measures to avoid criminal acts which at times can happen to anyone. Research application of journalistic ethics is intended to describe in concrete terms the implementation of the code of ethics of journalism on Crime News (news murders) in Pekanbaru daily MX. Subsequently, describe the factors that cause violations of the journalistic code of ethics.Data collection technique used observation, interview and documentation. Data analysis technique in this research is data analysis technique is a model of data analysis techniques Miles and Huberman interactive model. While the technique of data authenticity through the extension of participation and triangulation.Results of the analysis of documents and interviews showed that most of the journalistic code of ethics has been adopted by Pekanbaru MX causative factor has not fully implemented the code of ethics of journalism, among others: (1) situational aspects, (2) short reporting limit, and (3) that the newspaper enthused by readers. As a result there is a whole chapter on journalism ethics on crime news in Pekanbaru MX murder has not been implemented to the maximum by reporters and editors Pekanbaru MX.Key Words : Mass Media, Code Ethics Journalism, Crime News